DESIGN AND PROTOTYPE PRODUCTION OF UNINTERRUPTED CLEAR FRUIT JUICE PRODUCTION LINE WITH TANDEM FEED ULTRAFILTRATION METHOD - Altin-Golen, Cansu; Dİşlİ, Ebubekir; Mavuş, Rukiye (International Journal of Research -GRANTHAALAYAH, 2025)
In the fruit juice industry, ultrafiltration (UF) technology has gained great importance in the production of clear fruit juice in recent years. In this study, by determining the clogging period of the membrane with turbid product inlet and clear product outlet pressure in the UF membrane, the limit impurity value was determined and turbid product was fed accordingly. In this process, the dark product coming out of the membrane was stored in one of the tandem tanks and fed to an external decanter from this tank after a certain period of time. The clear product from the decanter was sent to the clear product tank feeding UF, which was still in production. Thus, the CIP process, which is mandatory in case of clogging of the membranes, was postponed and the diafiltration process was carried out externally, ensuring internal uninterrupted production. In addition, it was aimed to prevent fouling by surface modification with various polyelectrolytes for the membranes used in these processes. Clarity, iodine, alcohol, pH tests, brix measurement, SEM and contact angle analyses were performed on coated and uncoated membranes under 3 and 5 bar pressure. By delaying fouling, CIP process time was reduced and production time was increased. Thus, production efficiency was increased and CIP chemical costs and water consumption were reduced by shortening the CIP time and number. In addition, water consumption during the diafiltration process is prevented. The high efficiency and low cost of the developed system makes UF systems preferable and accessible.